The world of Indigenous North America - Warrior, Robert Allen (The Routledge worlds, 2015)
"The World of Indigenous North America is a comprehensive look at issues that concern indigenous people in North America. Though no single volume can cover every tribe and every issue around this fertile area of inquiry, this book takes on the fields of law, archaeology, literature, socio-linguistics, geography, sciences, and gender studies, among others, in order to make sense of the Indigenous experience. Covering both Canada's First Nations and the Native American tribes of the United States, and alluding to the work being done in indigenous studies through the rest of the world, the volume reflects the critical mass of scholarship that has developed in Indigenous Studies over the past decade, and highlights the best new work that is emerging in the field. The World of Indigenous North America is a book for every scholar in the field to own and refer to often"--